2019
DOI: 10.4136/ambi-agua.2381
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic mulching on drip irrigation management of cabbage cultivation

Abstract: Irrigation has been pointed out in recent decades as the major consumer of water. Considering the need for a rational use of water resources and the importance of mulching for planting, this study evaluated the effect of organic mulching (sugarcane straw) under soil water storage for cabbage crop development. This research was conducted at CCA/UFSCar, and the experimental design was a completely randomized design with four replications and two treatments with and without sugarcane straw. Water application was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…They also observed that the macronutrient content followed the sequence N>K>Ca>S>Mg>P, and micronutrients followed the sequence Fe>Mn>Cu>Zn>B. Differences in the crop management (e.g., nutrition, irrigation, genotype), as well as soil differences, can affect the results of the experiments; however, the differences between the results observed by Berça, Mendonça and Souza (2019) [16] and the results of the present study are probably due to the time of evaluation of the cabbage leaves. In both experiments, the macronutrients N, Ca and K, and the micronutrients Fe and Mn were the most accumulated by cabbage leaves.…”
Section: Figure 1 Cabbage Foliar Levels Of Magnesium (Left Graph) and Zinc (Right Graph) As A Function Of Potassiumcontrasting
confidence: 51%
See 1 more Smart Citation
“…They also observed that the macronutrient content followed the sequence N>K>Ca>S>Mg>P, and micronutrients followed the sequence Fe>Mn>Cu>Zn>B. Differences in the crop management (e.g., nutrition, irrigation, genotype), as well as soil differences, can affect the results of the experiments; however, the differences between the results observed by Berça, Mendonça and Souza (2019) [16] and the results of the present study are probably due to the time of evaluation of the cabbage leaves. In both experiments, the macronutrients N, Ca and K, and the micronutrients Fe and Mn were the most accumulated by cabbage leaves.…”
Section: Figure 1 Cabbage Foliar Levels Of Magnesium (Left Graph) and Zinc (Right Graph) As A Function Of Potassiumcontrasting
confidence: 51%
“…Berça, Mendonça and Souza (2019) [16] evaluated the levels of macro and micronutrients in cabbage leaves at harvest. They also observed that the macronutrient content followed the sequence N>K>Ca>S>Mg>P, and micronutrients followed the sequence Fe>Mn>Cu>Zn>B.…”
Section: Figure 1 Cabbage Foliar Levels Of Magnesium (Left Graph) and Zinc (Right Graph) As A Function Of Potassiummentioning
confidence: 99%
“…Both plant and plastic mulching reduce water consumption for irrigation by increasing the irrigation efficiency and reducing evapotranspiration, thus resulting in higher profitability (Berça et al, 2019;Carvalho et al, 2018;Lima et al, 2017).…”
Section: Pinto Et Al (2023)mentioning
confidence: 99%
“…However, more recent experiments report show that inorganic mulch material such as black plastic had significant effect on cabbage size and yield compare to organic mulch material such as wheat straw while no mulching gave least output (Chantal, 2021). Although, under greenhouse condition the productivity of cabbage was reported not to be affected by mulching but was efficient in reducing evaporation and increased the efficiency of water usage (Berca et al, 2019). The different application of mulching under different cultivation practices, types, their effects, techniques and advantages in specific situation makes this experiment important to establish the right approach to be recommended to cabbage farmers in the South West Nigeria who have recently taken an interest into commercial cabbage production (Agri farming, 2021).…”
Section: Introductionmentioning
confidence: 99%